Eric Liddell : something greater than gold - Benge, Janet, 1958-; Benge, Geoff, 1954- (Seattle, WA : YWAM Pub., 1998)
A biography of the Scottish missionary and runner who won a gold medal in the 1924 Olympics and went on to do missionary work in China.
Includes bibliographical references (page 201).
Keywords: Liddell, Eric, -- 1902-1945 -- Juvenile literature; Missionaries -- China -- Biography -- Juvenile literature; Missionaries -- Scotland -- Biography -- Juvenile literature; Runners (Sports) -- Scotland -- Biography -- Juvenile literature; Liddell, Eric, -- 1902-1945.; Missionaries; Runners (Sports); Liddell, Eric, -- 1902-1945; Missionaries; Runners (Sports); China; Scotland; Biography; Juvenile works